Demography and clinical profile of patients with chronic pancreatitis in a tertiary referral hospital in eastern India - Jena, Chandrakanta; Mohapatra, Minati; Panda, Srikant; Sarangi, Anshuman; Sarangi, Ashok K.; Babu, K. Kiran (International Journal of Research in Medical Sciences, 2022)
Background: Chronic pancreatitis is defined as a pathological fibro-inflammatory syndrome of the pancreas in individuals with genetic, environmental and/or other risk factors who develop persistent pathological responses to parenchymal injury or stress. Potential causes can include toxic factors (such as alcohol or smoking), metabolic abnormalities, idiopathic mechanisms, genetics, autoimmune responses and obstructive mechanisms. We studied the epidemiological patterns in relation to age, sex and socioeconomic status, the etiological factors and pattern of clinical presentations. the different modes of management of chronic pancreatitis. Methods: This prospective study on chronic pancreatitis was conducted in 55 patients admitted in Srirama Chandra Bhanja Medical College and Hospital (SCB M. C. H.), Cuttack, general surgery and surgical gastroenterology department. Results: In the study sample 37 patients (68%) were male and 18 patients (32%) were female. the etiological distribution of the study sample is shown. 29 patients (53%) showed topical etiology, 21 patients (37%) showed alcoholic and 5 patients showed idiopathic. The sign and symptoms (clinical) of the study sample, 54 patients (98%) showed abdominal pain, 26 patients (47%) had diabetes (type 2), 1 patient showed steatorrhea, 2 patients (4%) had jaundice, 2 patients (4%) had pseudocyst and 1 patient (2%) had ascites. Surgical drainage procedure performed on the patients 23 patients (42%) underwent Pvestow lateral (longitudinal) pancreatic jejunostomy, 18 patients (33%) underwent frey, 7 patients (13%) had lateral pancreatic jejunostomy,1 patient (2%) had V section, 1 patient (2%) underwent whipple, 3 patients (5%) had cystogastrostomy and cystodudenostomy and 2 patients (3%) underwent cholecystojejunostomy. Conclusions: The study revealed Puestow’s procedure was the most commonly performed surgical drainage procedure with satisfactory results.